2020 50th Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN) 2020
DOI: 10.1109/dsn48063.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Context-Aware Detection of Unsafe Events in Robot-Assisted Surgery

Abstract: Cyber-physical systems for robotic surgery have enabled minimally invasive procedures with increased precision and shorter hospitalization. However, with increasing complexity and connectivity of software and major involvement of human operators in the supervision of surgical robots, there remain significant challenges in ensuring patient safety. This paper presents a safety monitoring system that, given the knowledge of the surgical task being performed by the surgeon, can detect safety-critical events in rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…As for the lookahead time, the majority of reported methods relies on a variable number of future frames for robust recognition. While real-time performance or ability to predict future samples are not always needed and pursued, further efforts in this direction could broaden the applicability of such algorithms within the surgical theatre, supporting systems for surgical process monitoring and anomaly detection and prevention [21,61].…”
Section: A Robust Temporal Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the lookahead time, the majority of reported methods relies on a variable number of future frames for robust recognition. While real-time performance or ability to predict future samples are not always needed and pursued, further efforts in this direction could broaden the applicability of such algorithms within the surgical theatre, supporting systems for surgical process monitoring and anomaly detection and prevention [21,61].…”
Section: A Robust Temporal Modellingmentioning
confidence: 99%
“…Finally, an emerging and closely related research sub-field is represented by the detection and forecast of surgical errors in fine-grained gestures. It has been recently shown that common gesture-specific errors can be identified in real-time if provided with corresponding real-time gesture labels [21]. Public availability of error annotations [21] will hopefully stimulate future research in this relatively unexplored field, which is fundamental for several CAI implementations including workflow monitoring and surgical automation.…”
Section: Translational Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in sensing and computing technology, artificial intelligence, and data science, the next generation of Robot-Assisted Surgery (RAS) systems is envisioned to benefit from new capabilities for context-specific monitoring [31] and virtual coaching during simulation training as well as decision support and cognitive assistance during actual surgery to improve safety, efficiency, and quality of care [28]. State-of-the-art RAS systems and simulators are designed with data logging mechanisms to collect system logs, kinematics, and video data from surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to augment RAS systems and simulators with mechanisms to monitor the progress of surgical tasks, and provide early and context-specific feedback to surgeons on potentially suboptimal or unsafe motions that might lead to low performance scores in training or safety-critical events during surgery [31]. In this study, we take a step towards this goal by analyzing recorded dry-lab demonstrations of two common tasks (Suturing and Needle Passing) performed on the da Vinci Research Kit (dVRK) [14].…”
Section: Introductionmentioning
confidence: 99%